Ethics to match complexity in agricultural research for development. Issue 7 (3rd October 2019) - Carter, Lucy; Williams, Liana
ABSTRACT: International research-for-development initiatives seeking to tackle complex problems present a range of challenges and responsibilities. Meeting standards of ethical research practice is one of these. While practitioners may identify as being committed to ethical practice, the reality is far more complicated. This situation is particularly apparent in agricultural research for development (AR4D). This article reflects on the changing research landscape before using the experiences of a unique partnership to demonstrate how the authors moved beyond compliance-focused tasks towards collective reflection and planning for a broad range of ethical challenges. It concludes with suggestions for integrating ethics into the planning and implementation of development initiatives.